Precipitation in lean Mg–Zn–Ca alloys. (15th October 2022) - Schäublin, R.E.; Becker, M.; Cihova, M.; Gerstl, S.S.A.; Deiana, D.; Hébert, C.; Pogatscher, S.; Uggowitzer, P.J.; Löffler, J.F.
Abstract: While lean Mg–Zn–Ca alloys are promising materials for temporary implants, questions remain on the impact of Zn and Ca on the microstructure. In this context, the precipitation of Zn and Ca in Mg-1.5Zn-0.25Ca (in wt.%), initially extruded at 330°C, towards Mg–Ca binary precipitates or Ca–Mg–Zn ternary precipitates was probed in a multiscale correlative approach using atom probe tomography (APT) and analytical transmission electron microscopy (TEM). Particular focus was set on the ternary precipitate phase whose structure is debated. In the as-extruded material, the binary precipitates are made of hexagonal C14 Mg2 Ca containing up to about 3 at.% of Zn. The ternary ones are based on the hexagonal Ca2 Mg5 Zn5 prototype structure with a composition close to Ca3 Mg11 Zn4, as deduced from atomically resolved EDS mapping and scanning TEM imaging, supported by simulations. The precipitation sequence was scrutinized upon linear heating from room temperature to 375°C, starting from the solutionized material. Three exothermic differential scanning calorimetry (DSC) peaks were observed, at respectively 125, 250 and 320°C. Samples were taken after the peak decays, at respectively 205, 260 and 375°C for structural analysis. At 205°C, APT analysis revealed Ca-rich, Zn-rich and Zn‒Ca-rich clusters of about 3 nm in size and with a number density of 5.7  ×  10 23  m −3 . At 260°C, APT and TEM showed mono-layered Zn‒Ca-rich Guinier‒Preston (GP) zones of about 8 nm in size and with a number density of 1.3  ×  10 23  m −3 . At 375°C, larger and highly coherent elongated precipitates were found, with a size of about 50 nm. They occur as binary Mg–Ca precipitates or ternary Ca2 Mg6 Zn3 precipitates, as deduced from scanning TEM-based energy dispersive X-ray spectroscopy (EDS) and nanodiffraction in TEM. Here, the binary precipitates outnumber the ternary ones, while in the as-extruded material the ternary precipitates outnumber the binary ones, which corresponds well to the calculated phase diagram. We correlated the microstructure to hardness probed by Vickers testing. The largest hardening relates to the end of the 125°C DSC peak and thus to GP zones, which outperform the hardening induced by the nanometer-sized clusters and the larger intermetallic particles. The complexity of the precipitation sequence in lean Mg–Zn–Ca alloys is discussed. Graphical abstract: Image, graphical abstract